2022
DOI: 10.1111/inm.13053
|View full text |Cite
|
Sign up to set email alerts
|

Explanatory model of symptoms of stress, anxiety and depression in the general population: Cross‐sectional study during the COVID‐19 pandemic

Abstract: COVID‐19 pandemic has had a great impact worldwide, specially affecting mental health and has undoubtedly taken part in human behaviour modification, increasing global health burden and with stress, anxiety and depression being the main contributors to this load. Because of the importance of this issue, the objective of this study was the creation of an explanatory model for the causal relationship of the main psychological variables: stress, anxiety and depression in the COVID‐19 pandemic context. A cross‐sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Over time, the measures were gradually relaxed or eliminated, including lockdown, social distancing, wearing masks in specific locations, and changes to working conditions. This situation has had a significant impact on the mental health of the global population, with depression and anxiety being the most commonly reported symptoms ( 2 6 ). A study involving a large sample of the general Catalan population reported a threefold increase in the prevalence of depressive disorders (23%) and anxiety disorders (26%) compared to pre-confinement levels ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over time, the measures were gradually relaxed or eliminated, including lockdown, social distancing, wearing masks in specific locations, and changes to working conditions. This situation has had a significant impact on the mental health of the global population, with depression and anxiety being the most commonly reported symptoms ( 2 6 ). A study involving a large sample of the general Catalan population reported a threefold increase in the prevalence of depressive disorders (23%) and anxiety disorders (26%) compared to pre-confinement levels ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…A study involving a large sample of the general Catalan population reported a threefold increase in the prevalence of depressive disorders (23%) and anxiety disorders (26%) compared to pre-confinement levels ( 4 ). Studies describing the impact on mental health symptoms at the onset of the pandemic observed rates reaching 75% to 80% of the population ( 2 , 4 ). Patients with substance use disorder (SUD) are particularly vulnerable to the psychological effects of the social stressors caused by the pandemic ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%